The Protein-Sparing Modified Fast Diet: An Effective and Safe Approach to Induce Rapid Weight Loss in Severely Obese Adolescents - Bakhach, Marwan (Glob Pediatr Health, 2016)
Objectives: The protein-sparing modified fast (PSMF) is a rigorous way of rapidly losing a large amount of weight. Although adult studies have shown the PSMF to be effective, data in adolescents are lacking. The aim of this study was to determine the efficacy and safety of the PSMF in severely obese adolescents. Methods: 12 subjects who were evaluated in the Obesity Management Program at the Cleveland Clinic from 2011 to 2014 were included. The subjects were initiated on the PSMF after failing other conventional methods of weight loss. Once the goal weight was achieved, subjects were transitioned to the refeeding phase for weight maintenance. Results: Follow-up was scheduled at 3-month (11 patients) and 6-month (6 patients) intervals. At the 6-month follow-up visit, the average weight loss was 11.19 kg (95% confidence interval = -5.4, -27.8, P = .028), with average of 9.8% from baseline. Fifty percent of subjects had >5% weight loss and 20% had >10% weight loss. Four patients were lost to the follow-up (40%). An improvement was noted in total cholesterol and high-density lipoprotein. Due to a small sample size these results were not statistically significant. Side effects reported by subjects were mild dehydration due to nausea (2 patients), decreased energy (1 patient), and transient labile mood (1 patient). No life-threatening side effects were reported. Conclusion: Our results show that the PSMF diet can be used as an effective and safe method in the outpatient setting for rapid weight loss in adolescents with severe obesity.